THE ROLE OF SOCIAL CONSCIOUSNESS AND GENDER VIEWS IN THE FORMATION OF FAMILY AND MARRIAGE VALUES AMONG MEDICAL STUDENTS (Universal International Scientific Journal, 2026)
This article psychologically analyzes the role of social consciousness and gender views in the formation of values ​​related to family and marriage among medical students. It highlights socio-psychological factors that influence young people's perceptions of family, expectations from marriage, the distribution of family roles, and the formation of gender stereotypes.
Keywords: family; marriage; family values